Single-procedure 8Fr rheolytic pharmacomechanical thrombectomy for treatment of acute iliofemoral deep venous thrombosis - Nicholas Xiao; Matthew Genet; Rocio Marquez Karry; Elias Hohlastos; Jennifer Karp; Kush Desai (CVIR Endovascular, 2024)
Abstract Purpose We hypothesize that single-procedure venous-specific rheolytic thrombectomy for treatment of acute iliofemoral deep venous thrombosis (DVT) will result in improved clinical symptoms as measured by the venous clinical severity score (VCSS), as well as durable venous patency, with decreased hemorrhagic risks and costs associated with conventional catheter-directed therapy and prolonged lytic exposure. Materials and methods Thirty-three consecutive patients with symptomatic, unilateral, iliofemoral DVT who were treated with single-procedure therapy using the 8Fr rheolytic thrombectomy catheter were retrospectively analyzed from 2012–2021. Abstracted data included technical success (> 95% clearance of acute thrombus), adverse events (AEs), and clinical and imaging outcomes at 1-month and 1-year. Results Technical success was achieved in all 33 patients. Mean pre-procedure VCSS was 7.5 with mean edema and pain sub-scores of 2.6 and 1.8, respectively. Post-procedural total mean VCSS at one month was significantly improved (mean post-procedure VCSS = 0.3, mean reduction of 7.2, P < 0.01). Clinical improvement was sustained at 1-year (mean total VCSS = 0.2, P < 0.01). Primary patency was achieved in all patients at 1-month and 30 (91%) patients at 1-year. Among the 3 patients in which primary patency was not achieved at 1-year, primary-assisted patency was achieved in 2 patients. Secondary patency was achieved in the remaining patient at 1-year. No hemorrhagic AEs occurred in this study. Conclusion This study suggests that single-procedure venous-specific rheolytic thrombectomy for treatment of acute iliofemoral DVT is safe and effective, resulting in durable clinical and radiographic results at one year, while also limiting hemorrhagic risks, mitigating costs of admission, and expediting patient discharge.